ANALYSIS OF PERFORMANCE THREE TYPE PHOTOVOLTAICS (MONOCRYSTALLINE, POLYCRYSTALLINE, AND THIN FILM CIGS) IN THE REMOTE AREA, TROPICAL REGIONS, KARIMUNJAWA ISLANDS - EFENDI (NIM : 23115306), MUTIARA
Cell Photovoltaics (PV) is a technology that directly generate electricity from solar energy resource. The PV utilization can fulfil energy supply for the remote areas that are not powered to the main grid. The PV type can be selected based on the climate area to obtain a maximum and efficient energy production. In the tropical area, similar as the present study in the Desa Kamujan, Karimunjawa Islands, the PV testing was performed to determine the most effective one. The PV was tested on the building which was used by the fisherman for making ice. There are three types of the PV were used in this study with certain capacity: monocrystalline (2700 Wp), polycrystalline (2340 Wp), and thin film (200 Wp). The testing was taken for 31 days (January 2018 Ã‚Â– February 2018) in the rainy season in Karimunjawa. Each PV was analyzed by the module efficiency, power output efficiency, and performance ratio. The result of the study shows that monocrystalline has the highest module efficiency to 10,84%, followed by polycrystalline (10,65%) and thin film (6,8%). The power output efficiency of the PVs from the highest was thin film (18,8%), polycrystaline (15.15%) and monocrystalline (14,64%). While the performance ratio shows that the highest goes to polycrystalline (70,6%), followed by monocrystalline (62,58%) and thin film (55,11%).